2019
DOI: 10.1002/slct.201900764
|View full text |Cite
|
Sign up to set email alerts
|

Prolinamide‐Catalysed Asymmetric Organic Transformations

Abstract: Proline was reported as an enantioselective organocatalyst for direct asymmetric aldol reaction in the early 1971 s by two independent groups of researchers and the reaction was called the Hajos‐Parrish‐Eder‐ Sauer Wiechert reaction. The breakthrough of enantioselective organocatalysis was demonstrated by List and co‐workers in 2000 for intermolecular aldol reaction between benzaldehydes and ketone using proline as a catalyst. After this report many researchers were applied the proline as a catalyst for other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 198 publications
0
7
0
Order By: Relevance
“…(2) Replacing TFA with acetic acid enhanced catalyst activity at lower temperature, which might be attributed to the lower comparative acidity of acetic acid. 37 Thus, at 22 °C, 1 -SP and 1 -MCH + produced 70 and 3% yields of aldol products, respectively; however, the reactivity difference significantly diminished at 40 °C (entries 9–12). (3) Performing the reaction at elevated temperatures increased the activity of 1 -MCH + (entries 9–12 and 15–18).…”
Section: Resultsmentioning
confidence: 92%
“…(2) Replacing TFA with acetic acid enhanced catalyst activity at lower temperature, which might be attributed to the lower comparative acidity of acetic acid. 37 Thus, at 22 °C, 1 -SP and 1 -MCH + produced 70 and 3% yields of aldol products, respectively; however, the reactivity difference significantly diminished at 40 °C (entries 9–12). (3) Performing the reaction at elevated temperatures increased the activity of 1 -MCH + (entries 9–12 and 15–18).…”
Section: Resultsmentioning
confidence: 92%
“…Numerous organocatalytic enantioselective aldol reactions have successfully yielded chiral hydroxy ketones, utilizing small amino acids such as proline or its derivatives. Organocatalytic asymmetric cross-aldol reactions remain widely employed as a crucial tool in carbon–carbon bond formation reactions. , In our previous studies, we reported the use of various lipase enzymes in aldol reactions between different ketone and aldehyde species, achieving antiproducts with enantioselectivity ranging from 80 to 99% ee . Additionally, we described the enzymatic kinetic resolution of racemic 1,3-keto alcohols and biocatalytic hydrolysis of racemic 1,3-keto acetates, obtaining ( S )-β-hydroxy ketones with high enantioselectivities. The results of these works lead us to develop a new two-step asymmetric synthesis by the combined use of organocatalytic aldol reaction and asymmetric reduction.…”
Section: Introductionmentioning
confidence: 99%
“…But proline has some drawbacks as organocatalyst in asymmetric aldol reaction such as low solubility, low yields, and low enantioselectivity with aromatic aldehydes. So, the need for effective organocatalysts without these disadvantages has directed researchers' attention to develop new simple, effective catalysts, and various types of proline derivatives have been synthesized and applied to asymmetric aldol reaction [6]. Among them, the amide derivatives are a useful class of these types of catalysts.…”
Section: Introductionmentioning
confidence: 99%